1973
DOI: 10.1017/s0025315400056666
|View full text |Cite
|
Sign up to set email alerts
|

The meiofauna of a flatfish nursery ground

Abstract: Plates I-II and Text-figs 1-4)The meiofauna was studied over a 10-year period on a flatfish nursery ground between the high-water mark and a depth of 10 m below low-water springs.The sediment was well sorted sand, with median diameter from 210 to 279 ji in the intertidal area and 160 to 208 ji in the subtidal. It was composed of medium rounded quartz, with the calcium carbonate content mainly 0-25 to 2-20 % by weight. Porosity was 33-39% and the coefficient of permeability ranged from 166 to 233 x io~2 cm per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
1
1

Year Published

1976
1976
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(46 citation statements)
references
References 22 publications
4
40
1
1
Order By: Relevance
“…This suggests that the lower limit for interstitial life, excluding nematodes, is considerably lower than 200 JJ.m. The nematodes, however, are capable of sliding in very small spaces and it has been postulated that the lower limit for these forms is 125 JJ.m (Mcintyre & Murison 1973).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the lower limit for interstitial life, excluding nematodes, is considerably lower than 200 JJ.m. The nematodes, however, are capable of sliding in very small spaces and it has been postulated that the lower limit for these forms is 125 JJ.m (Mcintyre & Murison 1973).…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators have reported harpacticoid copepods to be unimportant to higher trophic levels (Marshal1 1970, McIntyre & Murison 1973, Heip & Smol 1976, but these studies are from unvegetated areas. More recent work from shallow water has shown that harpacticoids are a prevalent dietary item for some fishes, especially juveniles and smaller-sized species (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…These great density variations can probably be linked to the dispersion and/or migration of the animals within the sediment or through the water column. Nematode migration to deeper sediment layers during high tides has already been reported by many authors (e.g., MCINTYRE; MURISON, 1973;PLATT, 1977); however, STEYAERT et al (2001) found in a temperate estuary that some species have the opposite behavior, increasing their densities in the upper layers of the sediment during the submersion periods (high tides).…”
Section: Resultsmentioning
confidence: 70%